Envisioning Magic, A Princeton Seminar and Symposium. - Peter Schäfer; Hans Kippenberg (Editors) (Numen Book Series, 1997)
This collection of twelve articles presents a selection of papers delivered in the course of a seminar 1994-95 and its concluding international symposium at the Institute for Advanced Study in Princeton. The common theme is the interrelation between magic and religion, focussing particularly on the Mediterranean world in Antiquity - Egyptian, Graeco-Roman and Jewish beliefs and customs - but also treating the early modern period in Northern Europe (the Netherlands and Germany) as well as offering more general reflections on elements of magic in language and Jewish mysticism. The volume is characterized by an interdisciplinary approach and the use of varied methodologies, emphasizing the dynamic nature of the often contradictory forces shaping religious beliefs and practices, while dismissing the idea of a linear development from magic to religion or vice versa. The contributors are outstanding scholars in their fields: Ancient, Medieval and Modern History, Religious Studies, Jewish Studies, Classical Studies, Early Christianity, Islamic Studies, Anthropology, Egyptology and Comparative Literature. Without a doubt this re-evaluation of a fascinating age-old subject will stimulate scholarly discussion and appeal to educated non-specialist readers as well.